COVID-19 effects on risk minimising portfolio of Airlines companies using mean-CVaR model / Mohd. Aidil Sukarno, Awangku Zaidi Awang Zainal and Mohamad Eizhan Shahfizee Embok Mek - Sukarno, Mohd. Aidil; Awang Zainal, Awangku Zaidi; Embok Mek, Mohamad Eizhan Shahfizee (2022)
The global COVID-19 pandemic that occurred nowadays has significantly impacted Malaysia's stock market in every sector. Airline’s assets are part of the financial markets that have been affected by the outbreak. This study lies in finding the answers whether the mean-CVaR model effectively minimizes the risk for the portfolio of airlines assets. Therefore, this research aims to construct an optimum portfolio of airline assets. The closing price of the assets is obtained from the DataStream. The study samples involved 20 of airlines assets listed in Bursa Malaysia from 2010 to 2022. The scenario return obtained is used in the construction of 10 in-sample portfolios. An optimal portfolio is obtained by minimizing the risk using mean-CVaR with three target returns of 1.3%, 1.8%, and 2.3%, representing low, medium, and highreturns respectively. Then, answer to airline asset portfolio has the lowest risk in terms of CVaR as a risk measure whether before and during COVID-19. So, we were comparing risk behavior of the portfolio for airlines companies’ assets before and during COVID-19 pandemic.